2021
DOI: 10.3389/fnagi.2021.657095
|View full text |Cite
|
Sign up to set email alerts
|

Calcitriol Alleviates MPP+- and MPTP-Induced Parthanatos Through the VDR/PARP1 Pathway in the Model of Parkinson’s Disease

Abstract: The pathogenesis of Parkinson’s disease (PD) is currently unclear. Recent studies have suggested a correlation between vitamin D and PD. Vitamin D and its analogs have protective effects in animal models of PD, but these studies have not clarified the mechanism. Parthanatos is a distinct type of cell death caused by excessive activation of poly (ADP-ribose) polymerase-1 (PARP1), and the activation of PARP1 in PD models suggests that parthanatos may exist in PD pathophysiology. 1,25-Dihydroxyvitamin D3 (calcitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Another 6-OHDA study showed that cholecalciferol prevented characteristic losses in dopamine synthetic enzymes and transporters, preserved motor function as well as reduced lipid peroxidation [ 153 ]. Another study using MPTP showed co-administration with calcitriol improved motor deficits, reduced dopamine neuron toxicity and reduced ROS production [ 154 ]. The mechanism proposed was via an interaction between the liganded VDR and poly(ADP-ribose) polymerase-1(PARP1) to reduce its contribution to ROS-induced cell death.…”
Section: Vitamin D Is Neuroprotective In Neurons and Adult Brainmentioning
confidence: 99%
“…Another 6-OHDA study showed that cholecalciferol prevented characteristic losses in dopamine synthetic enzymes and transporters, preserved motor function as well as reduced lipid peroxidation [ 153 ]. Another study using MPTP showed co-administration with calcitriol improved motor deficits, reduced dopamine neuron toxicity and reduced ROS production [ 154 ]. The mechanism proposed was via an interaction between the liganded VDR and poly(ADP-ribose) polymerase-1(PARP1) to reduce its contribution to ROS-induced cell death.…”
Section: Vitamin D Is Neuroprotective In Neurons and Adult Brainmentioning
confidence: 99%
“…Biological extractions of BV2 cells and hippocampus were performed using RIPA lysis buffer, 1 mM PMSF, and 1× protease inhibitor cocktail (Sigma) as described previously [ 28 ]. The concentration of protein in the samples was determined using a Pierce™ BCA protein assay kit (Thermo Scientific™, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Besides, vitamin D could directly up-regulate the expression of C-Ret which is a multifunctional receptor vital for GDNF signaling in DA neurons, and increase the expression of GDNF which is important for the survival of DA neurons [ 40 ]. It has been proved that the activation of poly (ADP-ribose) polymerase-1 (PARP1) which contributes to the pathogenesis of PD in MPTP model, can be inhibited by overexpression of VDR [ 105 , 106 ]. Another experiment also found that over-expression of VDR could increase the expression of tyrosine hydroxylase (TH), catechol-o-methyl transferase (COMT), monoamine oxidase A (MAO-A), and vesicular monoamine transporter 2 (VMAT2) which can influence the differentiation of DA neurons [ 107 ].…”
Section: Effects and Molecular Mechanisms Of Vitamin D In Neurodegene...mentioning
confidence: 99%